Compressive Creep Performances of Dispersion Coated Particle Surrogate Fuel Pellets with ZrC–SiC Composite Matrix - Ren, Qisen; Liu, Yang; Fang, Runjie; Wu, Lixiang; Liu, Weiqiang (Materials, 2025)
Nuclear fuel pellets are subject to stress for long periods during the in-pile operation, and this study on high-temperature creep performance is of great significance for predicting the in-pile behaviors and safety evaluation of fuel elements. In the present study, a mixture of ZrC (50 wt%), SiC (46 wt%), and Si (4 wt%) powder was ball-milled for 24 h and then evaporated to obtain ZrC–SiC composite material. ZrC–SiC composite was adopted as the matrix, with ZrO2 surrogate kernel TRSIO particles and dispersion coated particle fuel pellets prepared with different TRISO packing fractions using the Spark Plasma Sintering (SPS) process. This study on compressive creep performances was conducted under a temperature range of 1373–2073 K and a stress range of 5–250 MPa, elucidating the creep behavior and mechanism of dispersed coated particles fuel pellets, and obtaining the variation laws of key parameters such as creep stress exponents and activation energy with TRISO packing fraction. The results showed that creep stress exponents of the surrogate fuel pellets are between 0.89 and 2.12. The activation energies for high temperature–low stress creep (1873–2073 K, 5–50 MPa) are 457.81–623.77 kJ/mol, and 135.14–161.59 kJ/mol for low temperature high stress creep (1373–1773 K, 50–250 MPa). Based on the experimental results, a high-temperature creep model was established, providing a valuable reference for the research and application of a ceramic matrix dispersed with coated particle fuels.